Selective suppression of AMP-activated protein kinase in skeletal muscle: update on 'lazy mice'. (1st February 2003) - Mu, J.; Barton, E.R.; Birnbaum, M.J.
Abstract : AMP-activated protein kinase (AMPK) is becoming recognized as a critical regulator of energy metabolism in cells. Using a mouse model in which we specifically blocked AMPK activity in muscles, we have demonstrated that activation of AMPK is necessary for the effects of 5-aminoimidazole-4-carboxamide riboside ('AICAR') and hypoxia, and is possibly required for a portion of exercise-induced glucose uptake. These same mice could not maintain sufficient glycogen in their skeletal muscle and it was rapidly depleted when the animals were subjected to mild exercise. Using isolated strips, we observed muscle hypertrophy and increased tiredness in the AMPK-deficient muscle. We also performed microarray analysis and showed dramatic changes of transcription profile in muscles of the lazy mice. These could have a significant impact on muscle function and may contribute to the observed phenotype.